Mito-Nuclear Communication by Mitochondrial Metabolites and Its Regulation by B-Vitamins - Janssen, Joëlle J. E.; Grefte, Sander; Keijer, Jaap; de Boer, Vincent C. J. (Frontiers in Physiology, 2019)
Mitochondria are cellular organelles that control metabolic homeostasis and ATP generation, but also play an important role in other processes, like cell death decisions and immune signaling. Mitochondria produce a diverse array of metabolites that act in the mitochondria itself, but also function as signaling molecules to other parts of the cell. Communication of mitochondria with the nucleus by metabolites that are produced by the mitochondria provides the cells with a dynamic regulatory system that is able to respond to changing metabolic conditions. Dysregulation of the interplay between mitochondrial metabolites and the nucleus has been shown to play a role in disease etiology, such as cancer and type II diabetes. Multiple recent studies emphasize the crucial role of nutritional cofactors in regulating these metabolic networks. Since B-vitamins directly regulate mitochondrial metabolism, understanding the role of B-vitamins in mito-nuclear communication is relevant for therapeutic applications and optimal dietary lifestyle. In this review, we will highlight emerging concepts in mito-nuclear communication and will describe the role of B-vitamins in mitochondrial metabolite-mediated nuclear signaling.